Adsorption Kinetics of Cd(II) From Aqueous Solution Using Surfactant Modified Activated Carbon-Sodium Lauryl Sulphate (SMAC-SLS) - Side, Sumiati; Putri, Suriati Eka; Perdana, Rini; Rahman, Abd. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
The purpose of this study was to determine the adsorption kinetic model of Cd(II) from aqueous solution using Surfactant Modified Activated Carbon-Sodium Lauryl Sulphate (SMAC-SLS). This study began by varying pH, contact time, and adsorbate concentration. The concentration of Cd(II) was measured using a spectrophotometric method. The results of the analysis showed that the optimum pH occurred at pH 5 with an adsorption percentage of 84.58±1.44% and the optimum contact time at 100 minutes with an adsorption percentage of 88.75±1.5%. Furthermore, in the variation of adsorbate concentration, the adsorption percentage decreased with increasing adsorbate concentration. The adsorption kinetics followed a pseudo second order with an R2 value of 0.9945 with an adsorption capacity of 8.89 mg/g. Thus, the use of SMAC-SLS as a future adsorbent for Cd(II) is highly recommended.